Prospective study to analyze clinico-epidemiological profile of patients presenting with liver abscess at tertiary care centers - Rampal, Kapil; Prajapati, Devendra K; Sharma, Meghna; Singh, Shakti Pratap (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: Liver abscess is an ancient disease bothering mankind since ages and continues to be a common health problem in India. Both of its subtypes i.e., amoebic and pyogenic, continues to pose serious challenge to the Indian health care system. Aims and objectives: To determine the demographic profile of patients, to assess type of liver abscess prevalent in the region and to assess etiological factors of the disease. Methods: Study was conducted in two tertiary care and referral hospitals in the Indian national capital region and a govt. hospital in Punjab from 01 July 2016 to 31 December 2019 and the patients were followed up till June 2020 with the last recruited patient getting a six month follow up. Diagnosis was confirmed by sonography and examination of aspirate. Positive routine bacteriological culture of the pus and a positive response to routine antibiotics made up for the pyogenic liver abscess category. Results: Liver abscess commonly affects middle aged males of low socioeconomic status. Diabetics and alcohol (both Indian made foreign liquor and the local country liquor) are biggest risk factors. Majority have raised leukocyte counts while Alkaline phosphatase is the most commonly deranged liver function test marker, raised to more than twice of the normal range in most cases. Right lobe involvement, right sided pleural effusion and raised right hemidiaphragm are seen in plain chest X-ray. Fever and pain abdomen are the most common presenting complaints. USG abdomen is an effective diagnostic modality that also serves to guide intervention procedures. Conclusions: Early diagnosis and timely intervention produces best results. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 473-477